A primate model of parkinsonism: selective destruction of dopaminergic neurons in the pars compacta of the substantia nigra by N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine. - Burns, R S (1983)
A syndrome similar to idiopathic parkinsonism developed after intravenous self-administration of an illicit drug preparation in which N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (NMPTP) might have been responsible for the toxicity. In the present study we show that intravenous administration of NMPTP to the rhesus monkey produces a disorder like parkinsonism (akinesia, rigidity, postural tremor, flexed posture, eyelid closure, drooling) that is reversed by the administration of L-dopa. NMPTP treatment decreases the release of dopamine and dopamine accumulates in swollen, distorted axons in the nigrostriatal pathway just above the substantia nigra, followed by severe nerve cell loss in the pars compacta of the substantia nigra and a marked reduction in the dopamine content of the striatum. The pathological and biochemical changes produced by NMPTP are similar to the well-established changes in patients with parkinsonism. Thus, the NMPTP-treated monkey provides a model that can be used to examine mechanisms and explore therapies of parkinsonism.